Musik Semar Pegulingan Menurunkan Kecemasan Pasien Pre Operasi di Siloam Hospitals Bali - Ni Putu Dian Yuniantari (Institut Seni Indonesia Denpasar, 2021)
Patients’ anxiety before surgery can interfere the operation even the patients can cancel the action to be performed. Semar pegulingan traditional music therapy can be used as an alternative to reduce anxiety. The study aimed to understand how the effect of Semar Pegulingan music on anxiety levels of presurgery patients in the Preparation Ward of Siloam Hospitals Bali. This study used quantitative methods, pre-experimental pretest-posttest with control design. The sample was presurgery patients using local anesthesia, selected by purposive sampling of 32 people. The sample was divided into a treatment and a control group each consisted of 16 people, selected by simple random. The pretest and posttest data were analyzed using Wilcoxon test, while the data between groups used Mann Whitney test at α 0.05. In the intervention group, the average of pre-anxiety level was 21.12 and 15.75 with p (0.001 <α (0.05). In the pre-test group, 21.81 and 18.50 in the post-test group, p (0.001 <α (0.05). Mann Whitney pre-test in the control and intervention groups obtained p value (0.153)> (0.05) and after the intervention obtained p value (0.01) <α (0.05). Semar Pegulingan music can reduce anxiety in presurgery patients. It is expected that semar pegulingan music is played in presurgery patients to reduce anxiety.